A randomized controlled trial with everolimus for IQ and autism in tuberous sclerosis complex. (9th July 2019) - Overwater, Iris E.; Rietman, André B.; Mous, Sabine E.; Bindels-de Heus, Karen; Rizopoulos, Dimitris; ten Hoopen, Leontine W.; van der Vaart, Thijs; Jansen, Floor E.; Elgersma, Ype; Moll, Henriette A.; de Wit, Marie-Claire Y.
Abstract : Objective: To investigate whether mammalian target of rapamycin inhibitor everolimus can improve intellectual disability, autism, and other neuropsychological deficits in children with tuberous sclerosis complex (TSC). Methods: In this 12-month, randomized, double-blind, placebo-controlled trial, we attempted to enroll 60 children with TSC and IQ <80, learning disability, special schooling, or autism, aged 4–17 years, without intractable seizures to be assigned to receive everolimus or placebo. Everolimus was titrated to blood trough levels of 5–10 ng/mL. Primary outcome was full-scale IQ; secondary outcomes included autism, neuropsychological functioning, and behavioral problems. Results: Thirty-two children with TSC were randomized. Intention-to-treat analysis showed no benefit of everolimus on full-scale IQ (treatment effect −5.6 IQ points, 95% confidence interval −12.3 to 1.0). No effect was found on secondary outcomes, including autism and neuropsychological functioning, and questionnaires examining behavioral problems, social functioning, communication skills, executive functioning, sleep, quality of life, and sensory processing. All patients had adverse events. Two patients on everolimus and 2 patients on placebo discontinued treatment due to adverse events. Conclusions: Everolimus did not improve cognitive functioning, autism, or neuropsychological deficits in children with TSC. The use of everolimus in children with TSC with the aim of improving cognitive function and behavior should not be encouraged in this age group. Clinicaltrials.gov identifier: NCT01730209. Classification of evidence: This study provides Class I evidence that for children with TSC, everolimus does not improve intellectual disability, autism, behavioral problems, or other neuropsychological deficits.